Peran Ghuruh Tolang dalam Menanamkan Nilai Karakter pada Santri di Musholla Al-Ismail Tanah Merah Bangkalan - Abdullah, Abdullah; Ismail, Moh. (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2019)
Discussing early education in Bangkalan, it is often associated with ghuruh tolang. Ghuruh tolang is an educator figure who plays an important role in the formation of children's basic character, but it is rarely studied and researched. This descriptive research seeks to analyze the role of ghuruh tolang in Instilling Islamic Character Values in Students at Al-Ismail Mosque Tanah Merah Bangkalan. The basic thing that ghuruh tolang does is to teach students to read the Qur'an starting from introducing the letters hijaiyah to be able to read the Qur'an. Findings of this study explained that the people of Madura (in this case in Tanah Merah Bangkalan) highly upholds ahklak and religion, because of that be a guide in life heading in a better direction. On this basis, ghuruh tolang instills character in students which includes three aspects, namely physical, psychiatry and spirituality carried out intensively and continuously